Analysis of Factors Determining Intra-ASEAN Product Trade Flows : Gravity Model Approach - Septiyanti, Ratih; Dalimunthe, Nina Rahmida; Asharuddin, Muh. (Jurnal Dinamika Sosial Ekonomi, 2025)
International trade encourages the creation of economic cooperation regionally. Integration of the ASEAN Economic Region by initiating the ASEAN Free Trade Area (AFTA) is expected to increase intra-ASEAN trade. However, the contribution of trade between ASEAN countries to ASEAN trade value has experienced stagnant growth and is still dominated by trade between countries outside the ASEAN region. The aim of this research is to determine the factors that influence trade flows between ASEAN countries so that they can encourage the value of trade between ASEAN countries. The data used in this research is panel data consisting of 10 ASEAN member countries for 17 years which is explained using a gravity model approach. The research results show that the GDP variables of exporting countries, population of export destination countries and trade openness have a significant positive influence on the value of trade between ASEAN countries. ASEAN countries need to consider a country's trade openness when formulating international trade policies in order to have a positive impact on increasing trade value.